Character Building Based on Local Culture - Mustakim Mustakim; Salman Salman (Edumaspul: Jurnal Pendidikan, 2019)
Character is an important aspect to human success in the future. Character education is now a major issue in education, apart from being part of the process of forming the morals of the nation's children, character education is also expected to be the main foundation in the success of Indonesia Gold 2025. This study aims to determine the application of local culture-based character education at SMAN 4 Enrekang and supporting and inhibiting factors of local culture-based character education and how the results of the application of local culture-based character education. This research was a qualitative descriptive study conducted at SMAN 4 Enrekang. Researcher collected data using interviews and documentation and analysis of data was qualitative analysis. The results of this study indicate that the students are less able to grasp the pattern of character education because of lack of discipline in their daily life habits and outside school, lack of awareness of students to respect their teachers so that the value of student character values decrease and lack of communication between teacher and students’ parents.